ANALISIS PERENCANAAN DAN PENGENDALIAN PERSEDIAAN DENGAN MENGGUNAKAN METODE ECONOMIC ORDER QUANTITY (EOQ) DAN PERIOD ORDER QUANTITY (POQ) - Uun Novalia Harahap; Yetti Meuthia Hasibuan; Abdul Azis Syarif; Agung Al Balad; Khairul Amri (Universitas Harapan Medan, 2022)
Supplies are always needed by every company, both small companies, and large inventories. Without an inventory of raw materials, the company is faced with the risk that one day the company will not be able to meet the needs of consumers. The purpose of this study is to determine the amount of raw material purchased at each message with the lowest cost and find out the right time period to place an order for raw materials by calculating with the raw method. The data studied is in the form of data on raw material needs, data on ordering costs, storage costs, frequency of raw material purchases, and the amount of raw material purchases during 2021. The approach used is the Economic Order Quantity (EOQ) and Period Order Quantity (POQ) Methods. Meanwhile, the calculation using the POQ method is lower than the company's policy, with the purchase of raw materials as many as 1,170 pallets with a frequency of 6 times, and 34 pieces of plywood with an order period made 10 times a year with a total inventory cost that must be spent of Rp. 4,581,178, or only 26% of the current method carried out by the company. By using the POQ method, the company can save inventory costs of Rp. 12,964,990. and safety supplies of 56 pallets and 6 sheets of plywood and re-ordered when the raw materials amounted to 1,296 pallets and 33 sheets of plywood. Based on the conclusions above, the author advises companies to consider using the POQ method to determine the need for raw materials needed.